Pharmaceutical Care with Multidisciplinary Team in Valve Replacement Patients at Warfarin Clinic, Maharat Nakhon Ratchasima Hospital - Paengthaisong, Amornrat; Jirapermpoon, Arisorn (Journal of Health Science of Thailand, 2018)
Warfarin therapy will be useful when the INR is in therapeutic range. A number of studies have shown that pharmacist managed anticoagulant clinic can improve clinical outcomes in patients; both for the improvement of anticoagulation control and reduction in major complications. As a result, a pharmaceutical care service was established at the Maharat Nakhon Ratchasima to improve anticoagulation control and reduce major complications. Patients were initially screened by nurse and subsequently seen by trained clinical pharmacists. Roles of pharmacist consisted of patient education, identification/resolution/prevention of drug-related problems (DRPs) along with the suggestion of appropriate dosage adjustment to physicians. Finally, physicians made treatment decision based on his/her judgments. Comparison of clinical outcomes was made between pre- and post-intervention period. During June 2003- September 2008, a total of 800 patients (3,704 visits) received pharmaceutical care services. Of a total of 1,639 DRPs, identified noncompliance was the most frequent problem (29.8%). Too low dosage and too high dosage accounted for 19.7 percent and 7.5 percent, respectively. On complications, bleeding and thromboembolism occurred in 17.8 percent and 0.3 percent of patients, respectively. Clinical pharmacists provide 2,129 recommendations on dosage adjustment to physicians of which 89.5 percent was accepted. The rate of major bleeding was found 4 and 8 events with mean follow up period was 0.36 and 1.56 patient-year in pre- and post-interventions, represent 1.32 and 0.64 per 100 patient-year. In addition, thromboembolism complications occurred 6 events and 5 events, represent 1.97 and 0.4 per 100 patient-year. From the total number of INR measurements pre- and post-interventions of 2,243 and 6,113 times, respectively, incidence of INR > 5 were 4.5 percent and 2.5 percent, respectively. Moreover, incidence of INR < 1.5 were 26.7 percent and 18.4 percent in the pre- and post-interventions, respectively. Among 453 patients with INR measurements not less than 2 times in both periods, INR target achievement was significantly increased from 40.87 percent to 52.43 percent in the pre- and postinterventions periods. Moreover, the proportion of patients with low INR variability (times in therapeutic range not less than 70 percent of monitored duration) significantly increased from 18.76 percent to 27.59 percent. In conclusion, pharmaceutical care with multidisciplinary team approach can lead to an improvement in anticoagulation control and decrease major bleeding and thromboembolic complications.